Unlocking the power of OPNET modeler - Lu, Zheng; Yang, Hongji (Cambridge : Cambridge University Press, 2012)
'For fast, easy modeling, this practical guide provides all the essential information you need to know. A wide range of topics is covered, including custom protocols, programming in C++, External Model Access (EMA) modeling and co-simulation with external systems, giving you the guidance not provided in the OPNET documentation. A set of high-level wrapper APIs is also included to simplify programming custom OPNET models, whether you are a newcomer to OPNET or an experienced user needing to model efficiently. From the basic to the advanced, you will find topics are easy to follow with theory kept to a minimum, many practical tips and answers to frequently asked questions spread throughout the book and numerous step-by-step case studies and real-world network scenarios included'--Provided by publisher.
Pt. 1. Preparation for OPNET modelling. Introduction ; Installation of OPNET modeler and setting up environments ; OPNET modeler interface -- pt. 2. Modelling custom networks and protocols. OPNET programming interfaces ; Creating custom models by using OPNET API packages ; High level wrapper APIs ; Create custom models by using high level wrapper APIs -- pt. 3. Modelling and modifying standard networks and protocols. Modelling standard wired networks and protocols ; Modelling standard wireless networks and protocols ; Principles and rules for modifying standard models ; pt. 4. OPNET modelling facilities. Debugging simulation ; OPNET programming in C++ ; Hybrid simulation and analytical simulation ; External model access (EMA) capabilities in OPNET Modeler ; OPNET co-simulation with third party programs ; Model authoring and security.
Includes bibliographical references (p. 236) and index.
Keywords: OPNET; Computer networks -- Mathematical models; Computer networks -- Simulation methods; Computer network protocols